2021
DOI: 10.1007/s00520-021-06472-7
|View full text |Cite
|
Sign up to set email alerts
|

Netupitant/palonosetron without dexamethasone for preventing nausea and vomiting in patients with multiple myeloma receiving high-dose melphalan for autologous stem cell transplantation: a single-center experience

Abstract: Chemotherapy-induced nausea and vomiting (CINV) is one of the most frequent adverse events compromising quality of life (QoL) in patients undergoing autologous stem cell transplantation (ASCT). However, CINV prophylaxis is still lacking uniformity for high-dose melphalan (HDM), which is used to condition patients with multiple myeloma (MM). Netupitant/palonosetron (NEPA) is administered with dexamethasone (DEXA) for CINV prevention in several chemotherapy regimens. Our study aims to assess the efficacy of NEPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…The findings from both studies indicated that the majority of patients did not experience emesis during both the acute and delayed phases (13,14). Another observational study reported the effectiveness of multidose NEPA during high-dose melphalan chemotherapy, with an impressive 93.3% of patients achieving CR (15). It is worth noting that the aforementioned studies utilized a three-dose regimen of NEPA.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The findings from both studies indicated that the majority of patients did not experience emesis during both the acute and delayed phases (13,14). Another observational study reported the effectiveness of multidose NEPA during high-dose melphalan chemotherapy, with an impressive 93.3% of patients achieving CR (15). It is worth noting that the aforementioned studies utilized a three-dose regimen of NEPA.…”
Section: Discussionmentioning
confidence: 95%
“…Two phase II clinical trials investigated the use of NEPA in patients receiving BEAM (carmustine + etoposide + cytarabine + melphalan) or FEAM (fotemustine + etoposide + cytarabine + melphalan) chemotherapy (13, 14). Additionally, two observational studies described its effectiveness during high-dose melphalan chemotherapy (15,16). However, these studies primarily focused on specific chemotherapy regimens, which may not adequately represent the diverse and complex conditioning regimens used prior to HSCT, particularly those involving multiday high-dose chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…В связи с этим в комбинации с апрепитантом доза дексаметазона должна быть снижена приблизительно на 50 %. У пациентов, получающих варфарин, необходимо дополнительно контролировать уровень МНО [87][88][89][90][91][92]. Антагонисты NK1-рецепторов применяют в комбинации с ГКС и антагонистами 5-НТ3-рецепторов.…”
Section: антагонисты Nk1-рецепторовunclassified
“…In adults, the use of a dexamethasone-free approach consisting in the administration of a netupitant-palonosteron combination or in the substitution of dexamethasone with olanzapine was shown to have similar efficacy as the use of dexamethasone; however, prospective data are awaited for children [43].…”
Section: Dexamethasonementioning
confidence: 99%